Impelementasi Pendidikan Karakter Pada Peserta Didik Di Sekolah Dasar - Yola Adelya Azhari; Nabilah Assyifa Lubis; Irda Yani Dongoran; Syahrial Syahrial (Journal on Education, 2024)
Character education is something that is very important and is a common focus, one of which is in the field of education. Character education must be prepared and implemented from an early age and can be implemented at elementary school level students. Character education for elementary school students is an effort or effort to prepare a generation that has character that can bring change to the nation and country of Indonesia for the better. Therefore, character education must be truly implemented so that the hope is that in the future students will have character that is in accordance with religious teachings and be able to face more complex future challenges. The challenge for character formation is the development of technology and information. The development of technology and information makes it easy for negative foreign culture to be absorbed without a strong filter. External culture is a modern lifestyle that influences attitudes and behavior that are unconsciously deviating from the values ​​and nobility of the Indonesian nation. The growing phenomenon of students who do not heed ethical values. The failure of schools to grow people with character is because they only prioritize students' cognitive or academic abilities. The implementation of character education in elementary schools has not been carried out consistently. This research aims to examine the implementation of character education in elementary schools. This research uses a qualitative approach with library methods. Data analysis techniques are carried out interactively. Data collection techniques are listening and taking notes. Data validity uses triangulation of data sources and adequacy of references.